1989
DOI: 10.3109/02656738909140458
|View full text |Cite
|
Sign up to set email alerts
|

Temperature distributions, microangiographic and histopathologic correlations in normal tissue heated by ferromagnetic needles

Abstract: Rabbit hind limb musculature implanted with nine ferromagnetic nickel-copper alloy needles was inductively heated in a 120 kHz oscillating magnetic field. Rabbits were heated every third day for a total of three 30 min heating periods. Ferromagnetic needles with Curie points of 42 degrees C, 45 degrees C, and 48 degrees C were used. Fourteen days following the third heating the animals were sacrificed and the tissues processed for microangiography and histopathology. Implanted muscle heated rapidly and achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…The above observations allow us to conclude that temperatures up to 50mC have no or minor effects on LECs in a capsular bag model, that 55mC is a near threshold temperature and that heating at 60mC is needed to destroy the whole population of LECs. These conclusions are in contrast with the observations of Partington et al(1989), who found that other tissues only tolerate temperatures up to 45mC. LECs are apparently more resistant to hyperthermia.…”
contrasting
confidence: 56%
“…The above observations allow us to conclude that temperatures up to 50mC have no or minor effects on LECs in a capsular bag model, that 55mC is a near threshold temperature and that heating at 60mC is needed to destroy the whole population of LECs. These conclusions are in contrast with the observations of Partington et al(1989), who found that other tissues only tolerate temperatures up to 45mC. LECs are apparently more resistant to hyperthermia.…”
contrasting
confidence: 56%
“…In contrast to methods relying on modifying the energy source to generate heat, there is evolving interest in methods to preferentially enhance the heat generating capacity of the cancer tissues by introducing exogenous materials in to them. Along these lines, ferromagnetic seeds have been used in conjunction with a magnetic field to induce hyperthermia in prostate cancer (Brezovich and Meredith 1989; Meredith et al 1989; Partington et al 1989). Ferromagnetic seeds or thermoseeds are needle-shaped devices that are interstitially placed into the tumor, similar to brachytherapy implants, and the heating is accomplished by an externally applied magnetic field.…”
Section: Hyperthermia For Prostate Cancermentioning
confidence: 99%
“…Ferromagnetic seeds or thermoseeds are needle-shaped devices that are interstitially placed into the tumor, similar to brachytherapy implants, and the heating is accomplished by an externally applied magnetic field. The uniqueness of thermoseed hyperthermia are (i) the lack of requirement for external power connections and (ii) the automatic regulation of temperature of the implanted thermoseeds depending on the compositional characteristics of the implants (Meredith et al 1989; Partington et al 1989). Being an interstitial modality, thermoseed mediated hyperthermia has limitations similar to other interstitial hyperthermia techniques.…”
Section: Hyperthermia For Prostate Cancermentioning
confidence: 99%